2012
DOI: 10.1177/03946320120250s109
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Upper Limb Spasticity after Stroke: One-Year Safety and Efficacy of Botulinum Toxin Type A NT201

Abstract: A new preparation of botulinum toxin type A called NT 201, free from complexing proteins, potentially with low antigenicity has been used in the therapy of spasticity in stroke patients. This was an open-label study reported the safety and the efficacy of one-year treatment with NT 201 evaluating the therapeutic effect on functional disability and on quality of life in upper limb spasticity after stroke. Patients received a botulinum toxin therapy in the upper injected intramuscularly. After inoculation, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…One of these studies explored the safety and efficacy of incobotulinumtoxinA in upper-limb post-stroke spasticity over a 1-year period in 20 patients who could receive retreatment every 12 weeks. 27 One year after the initial incobotulinumtoxinA treatment, muscle tone, determined using the MAS, was significantly reduced in all muscle groups treated ( P <0.001). In addition, DAS scores and daily spasm frequency were also significantly reduced ( P <0.001 for all).…”
Section: Clinical Efficacy and Safetymentioning
confidence: 87%
“…One of these studies explored the safety and efficacy of incobotulinumtoxinA in upper-limb post-stroke spasticity over a 1-year period in 20 patients who could receive retreatment every 12 weeks. 27 One year after the initial incobotulinumtoxinA treatment, muscle tone, determined using the MAS, was significantly reduced in all muscle groups treated ( P <0.001). In addition, DAS scores and daily spasm frequency were also significantly reduced ( P <0.001 for all).…”
Section: Clinical Efficacy and Safetymentioning
confidence: 87%
“…Patients are evaluated in an interview format, enabling the severity of the disability to be assessed (Table 1). Most studies involving DAS evaluations before and after BoNT-A administration [4][5][6][7][8][9][10][11][12][13][14][15][16][17] have focused on one treatment target from among the four DAS parameters. Simpson et al [7] reported that DAS scores improved significantly 6 weeks after BoNT-A administration in 19 patients who chose limb position as the target out of a total of 60 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Ade-Hall en el 2000 realiza una revisión bibliográfica donde se aconseja el uso de toxina para el control de los espasmos y espasticidad en niños con parálisis cerebral 184 . También encontramos otros artículos donde se evidencia la mejoría de los espasmos diarios tras la aplicación de toxina tanto en extremidad inferior 199 cómo en superior tras daño cerebral adquirido 200 .…”
Section: Valoración De La Calidad De Vida De Nuestros Pacientesunclassified